Association between psoriasis and peripheral artery occlusive disease: a population-based retrospective cohort study - Yeh, Chao-Bin; Yeh, Liang-Tsai; Yang, Shun-Fa; Wang, Bo-Yuan; Wang, Yu-Hsun; Chan, Chi-Ho (Frontiers in Cardiovascular Medicine, 2023)
Psoriasis (PSO) is a chronic skin disease associated with various diseases, particularly those that affect the cardiovascular system. This study explored whether peripheral artery occlusive disease (PAOD) is associated with PSO. This study was a retrospective cohort study from 2000–2018. The study population was newly diagnosed with PSO. The comparison group was defined as having never been diagnosed with PSO. The outcome variable was the diagnosis of PAOD. Propensity score matching was performed by age, sex, and comorbidities between the two groups. Kaplan–Meier analysis was used to calculate the cumulative incidence of PAOD among the two groups. To measure independent risk factors of PAOD, the Cox proportional hazards model was used to estimate hazard ratios. In total, 16,054 patients with PSO and 1,887,483 patients with no history of PSO were selected from Taiwan's longitudinal health insurance database, which includes the data of 2 million beneficiaries. After comparing propensity scores between the PSO and non-PSO groups for age, sex, and comorbidities, 15,696 patients in each group were analyzed for PAOD risk. The risk of PAOD for the PSO group was greater than that for the non-PSO group (HR = 1.25; 95% CI = 1.03–1.50). In the 40–64 years age group, the PSO group exhibited a higher risk of developing PAOD than the non-PSO group. In conclusion, patients with PSO have an increased risk of PAOD and curative care is necessary to reduce the risk of PAOD.